MCSE : - Moncur, Michael G (O’Reilly, 1998)
This detailed reference is aimed at sophisticated users who need a bridge between real-world experience and the MCSE exam requirements. Each chapter covers one exam and includes a summary of what it covers, a description of the exam format and difficulty with tips for passing it, definitions of key terms, and sample test questions and answers.